Comparative evaluation of xenobiotics in human and dietary milk: persistent organic pollutants and mycotoxins - Tsakiris, I. N.; Kokkinakis, E.; Dumanov, J. M.; Tzatzarakis, M. N.; Flouris, A. D.; Vlachou, M.; Tsatsakis, A. M. (Cellular and Molecular Biology, 2013)
Publications produced over the past 20 years regarding the concentration of xenobiotics in human and dietary milk were evaluated, focusing primarily on persistent organic pollutants (e.g. polychlorinated biphenyls, flame retardants), pesticides (e.g organochlorine) and mycotoxins. In general, countries of low industrialization rate present low levels of dietary milk contamination with dioxins compared to those with high rate of industrialization. According to published data, the most common persistent organic pollutants detected in breast and dietary milk are dichlorodiphenyltrichloroethane compounds, hexachlorocyclohexane, and hexachlorobenzene. Even though the potential risks of persistent organic pollutants in human milk have been acknowledged, the beneficial effect of breastfeeding as the optimal food source for newborn babies should not be disregarded. Especially when sharing information with the general public, it should be made clear that the presence of dioxins and persistent organic pollutants in human milk is not an indication for avoiding breastfeeding. The implications of xenobiotics in human and dietary milk is a matter of growing importance and warrants future work given its important health effects.